The "European zygomatic fracture" research project: The epidemiological results from a multicenter European collaboration. Issue 4 (April 2019) - Brucoli, Matteo; Boffano, Paolo; Broccardo, Emanuele; Benech, Arnaldo; Corre, Pierre; Bertin, Helios; Pechalova, Petia; Pavlov, Nikolai; Petrov, Petko; Tamme, Tiia; Kopchak, Andrey; Hresko, Andrii; et al.
Abstract: Purpose: Fractures of the zygomaticomaxillary complex (ZMC) are common injuries that may lead to loss of an aesthetically pleasing appearance and functional impairment. The aim of this study was to analyze the demographics, causes, characteristics, and outcomes of zygomatic fractures managed at several European departments of oral and maxillofacial surgery. Materials and methods: This study is based on a multicenter systematic database that allowed the recording of all patients with ZMC fractures between 1 January 2013 and 31 December 2017. The following data were recorded: gender, age, personal medical history, etiology, side of zygomatic fracture, classification of ZMC fracture, associated maxillofacial fractures, symptoms at diagnosis, type of performed treatment, and sequelae/complications. Results: A total of 1406 patients (1172 males, 234 females) were included in the study. Statistically significant correlations were found between assault-related ZMC fractures and the A3 class (p < .0000005) and between Infraorbital Nerve (ION) anesthesia and B class (p < .00000005). Conclusion: The most frequent cause of ZMC fractures was assault, followed by falls. The most frequently involved decade of age was between 20 and 29 years. The decision and type of surgical treatment of ZMC fractures depends on several issues that need to be considered on a case by case basis.